Comparative Study of Different Fixation Techniques in Distal Radius Fractures: A Systematic Review and Meta-analysis - Muhammad Saqib, Tauseef Raza, Osama Bin Zia, Aman Ullah Khan Kakar, Abdul Rauf Tippu, Akkad Rafiq, Aimal Sattar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This systematic review compared results of nonsurgical and surgical distal radius fracture therapy. Methods: A thorough search of the literature was carried out utilizing a number of databases, such as Medline, Embase, and Cochrane. Using the following Boolean operators, all databases were searched from the records of 2012-2023: distal radius fracture, conservative therapy, nonoperative treatment, surgical treatment, and operative. In order to compare the functional results of the surgical and nonsurgical groups, we collected all prospective and retrospective controlled studies. Results: From the available research, seven were prospective studies and seven were comparative retrospectives. We enrolled a total of 1310 patients; 655 were assigned to the nonsurgical group and 655 to the surgical group. In terms of DASH, grip strength, and the majority of other functional evaluations, the two therapy modalities had comparable outcomes. Rang of wrist flexion, ulnar variance, radial length, and radial inclination were all significantly different. Conclusion: According to this meta-analysis, compared to nonsurgical treatment, surgical treatment for distal radius fractures reduced the DASH score and increased the range of wrist supination and pronation in certain patients. This meta-analysis lends credence to the idea that distal radius fracture surgery may be the best option for certain individuals. Keywords: Distal radius fracture; Meta-analysis; Nonsurgical; Surgical